Journeys through Calabria between 19th and 20th century. Three case studies about transition from “Grand Tour” to modern tourism: Cesare Malpica, Luigi Vittorio Bertarelli e Bernard Berenson - Vittorio Cappelli (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
This essay aims to provide an interpretation of the slow shift from “Grand Tour” to modern tourism by considering the case of some journeys around Calabria. For this purpose, three exemplary cases were selected and analysed. First, the one of Cesare Malpica that travelled in Calabria in the 1840s, sitting in a litter, by coach and even on mule-back. Secondly, the journey of Luigi Vittorio Bertarelli, who travelled across Calabria by bicycle towards the end of the 19th century. Thirdly, Bernard Berenson‘s journeys, who visited Calabria by car twice. First time in 1908 and, after almost an half century, the second time in 1955.